Аssessment of the level of adaptive capacity of newborns with perinatal hypoxic CNS lesions by determining the level of neurospecific enolase in blood serum and heart rate variability - Boiarska, L. M.; Kravets, L. V.; Ivanova, K. O.; Боярская, Л. Н.; Кравец, Л. В.; Иванова, Е. А.; Боярська, Людмила Миколаївна; Кравець, Людмила Володимирівна; Іванова, Катерина Олексіївна (Polska: Warszawa, 2021)
В статье приведены результаты динамического изучения уровня нейроспецифической энолазы в сыворотке крови новорожденных детей с гипоксическим перинатальным поражением ЦНС и утановления корелляционой связи с изменением вариабельности сердечного ритма. Получены данные для оценки степени поражения гематоэнцефалического барьера и тяжести нарушения механизмов адаптации у детей рожденных преждевременно на разных сроках гестации. The article presents the results of a dynamic study of the level of neurospecific enolase in the blood serum of newborns with hypoxic perinatal CNS damage and the establishment of a correlation relationship with changes in heart rate variability. Data were obtained to assess the degree of damage to the blood-brain barrier and the severity of disorders in adaptation mechanisms in children born prematurely at different stages of gestation.
Оцінка рівня адаптаційних можливостей новонароджених дітей з перинатальним гіпоксичним ураженням ЦНС за допомогою визначення рівня нейроспецифічної енолази в сироватці крові та варіабельності серцевого ритму
Keywords: новорожденные; нейроспецифическая энолаза; недоношенность; вариабельность сердечного ритма; адаптация; newborns; neurospecific enolase; prematurity; heart rate variability; adaptation